(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The development of cognitive abilities of future sports coaches is a pedagogical and psychological process aimed at strengthening their mental processes, such as attention, memory, thinking, and decision-making. High cognitive abilities allow coaches to effectively analyze complex situations, plan training sessions, and communicate effectively with players. Active learning, reflective exercises, and self-assessment are used as pedagogical methods. Psychological support, stress management, and increased motivation also contribute to the improvement of cognitive processes. As a result, the development of cognitive abilities increases the professional potential of sports coaches and positively influences the success of sports teams.